Effect of bovine colostrum supplementation on respiratory tract mucosal defenses in swimmers - Crooks, C.; Cross, M. L.; Wall, C.; Ali, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
Prpose: This study investigated the effect of bovine colostrum (BC) on mucosal defense in the respiratory tracts of athletes and a nonexercising control group. Methods: An athlete cohort (ATH) of 25 (12 male, 13 female) elite swimmers (age 14-23 yr) and a control cohort (CON) of 28 (9M, 19F) students (age 18-27 yr) were randomly allocated in a double-blind manner to receive either 25 g BC (low-protein colostrum powder) or isocaloric placebo (PL) per day for 10 wk. Postprandial saliva samples were analyzed for immunoglobulins (A, G, and M) and osmolality at baseline, after 4 and 10 wk, and 2 wk postsupplementation. Blood samples were analyzed for immunoglobulins and C-reactive protein at baseline, after 5 and 10 wk, and 2 wk postsupplementation. Dietary intake was assessed by self-recorded dietary records. Upper respiratory tract symptoms (URS) and exercise were also self-recorded daily. Results: There was no significant time-related effect of the BC supplement on either saliva or plasma immunoglobulin levels for either cohort. After 4 wk supplementation fewer ATH/BC (25%) than ATH/PL participants (61%) reported URS incidents (p = .062). No significant difference occurred in URS reports in the control group. Conclusion: There was no measurable effect on immunoglobulin levels of consuming BC, which is in contrast to effects that have been reported previously in marathon runners, indicating that the effect of BC supplementation is not universal in all groups of athletes. Fewer athletes reported URS (although cause unknown) when consuming BC, which may be advantageous for training.